World Commodity Prices 1999 - 2000 - Klaus Matthies; Hans-Joachim Timm (Hamburg Institute of International Economics (HWWA), 1999)
The decline of most world commodity prices came to an end in recent months. The aggregate dollar price level was 15 per cent lower in the first quarter of 1999 compared to a year previously, and since autumn 1997 it even decreased by about 30 per cent. Oil prices fell particularly sharply, but quotations began to pick up strongly in March in anticipation of further production cuts. The price index for non-energy commodities, on the other hand, decreased only slightly since last October, although prices for food items - oilseeds, sugar and tropical beverages - sank again markedly this year. The decline in industrial commodity prices largely came to a standstill in the final months of last year, but there has as yet been no recovery. This is primarily due to a subdued demand from processors of industrial commodities following the slowdown of world economic growth. In the case of several commodities, weak prices are fostered by abundant supplies. Commodities continue to be available in ample global supply, whereas raw materials demand, in spite of an expected stabilisation of the situation in Asia's emerging economies and the start of recovery in Japan, will expand only slowly. As a consequence only a small increase in commodity prices is expected in the forecast period.
Keywords: 330; Rohstoffpreis; Prognose; Welt